Threadfin bream fishery and biology of Nemipterus japonicus off Veraval - Gopal, C; Vivekanandan, E (Indian Journal of Fisheries, 2011)
The annual average threadfin bream landings from 50 252 trawl units was 1 928.5 tonnes in Veravalduring April 1S87 — March 1990. The catch per unit effort was high during December - March. Nemipterusjaponicus, whi:h formed 82.6% of the threadfin bream landings, matured at 180 mm total length. The vonBertalanffy growth parameters were K = 0.733, t„ = - 0.1167 and L_ = 337 mm. N. japonicus preferred tofeed on crustaceans especially Aceles spp